Hubungan Terpaan Konten Akun Instagram @vinamuliana Dengan Pengetahuan Tentang Dunia Kerja Bagi Followers - Hanifah, Nida Firyal; Suryo, Herning; Siswanta, Siswanta (Solidaritas, 2024)
This study has two problem formulations, namely whether there is a relationship between exposure to @vinamuliana Instagram content and knowledge about the world of work for followers. The purpose of this study is to determine and explain whether there is a relationship related to exposure to @vinamuliana Instagram content with knowledge about the world of work for followers. The theory used in this study is the S-O-R Theory by McQuail (Stimulus, Organism, Response). This study also uses quantitative research methods with a type of correlation quantitative research approach. With the results of the study stating the value (rcount) 0.611> 0.196 (rtable) with a significance of 5% for 99 respondents, the working hypothesis (H1) is accepted and the null hypothesis (Ho) is rejected. The correlation coefficient value is 0.611, so there is a positive correlation between the relationship between content exposure (X) and follower knowledge (Y) regarding knowledge in the world of work which has a strong relationship between the two variables. With a coefficient of determination of = r or = 0.373321 (37%). The results show that: The results of related research prove that: (1) There is a relationship between exposure to @vinamuliana Instagram account and knowledge about the world of work for followers, (2) The level of influence of exposure to @vinamuliana Instagram content has a significant effect on knowledge about the world of work for followers by 37%. Keywords: Content Exposure, Instagram, Knowledge